Flood exposure assessment in Rivers State, Nigeria - M .Menegbo, Emmanuel; J. Emengini , Ebele (International Journal of Physical Research, 2023)
The primary procedure in emergency response and disaster risk management is identifying the scope of a natural hazard, such as determining regions at high risk. After this, exposure mapping helps estimate the disaster's potential impact - for instance, determining the number of possible people or facilities affected. Employing Earth Observation (EO) data gathered from satellites is commonly used to map areas with a high susceptibility to natural disasters. The purpose of this work was to evaluate flood exposure in Rivers State. The objectives included assessing the probable effects on local and urban settlement, and establishing the magnitude of damage on farmland. The research leverages multiple data sources, including Globalland 30, Global Human Settlement Population Layer. Quantum GIS played a significant role in assessing the vulnerability and exposure scale of both people and farmlands to flood risks. The primary analyses conducted involved zonal statistics and overlaps analysis. The study shows an estimated 161,537 people are impacted by this exposure. The flooding affects farmlands that cover approximately 5,591 hectares. Furthermore, estimated urban-rural area impacted by flooding is around 29,775,178 square meters, or 2,978 hectares This is executed largely for risk management or emergency response after events like floods, wind storms or landslides. For managing risks prior to a disaster, it's crucial to compare varying damage models with the corresponding exposure, delivering a comprehensive outlook on potential impacts.